Game-Based Elicitation of Spontaneous Speech in the Context of Pronunciation Practice Among Polish Intermediate Learners of English as a Foreign Language - Gajewska, Klaudia (Ludicity in (Glotto)Didactic, 2020)
The objective of the current article is to find out which of the three genres differing in the level of the spontaneity – a read-aloud task, presentation or spontaneous speech – has a positive influence on the quality of the students’ pronunciation with regard to a set of selected lexical items. Moreover, it aims to discover whether the types of utterances produced by EFL learners affect their emotional well-being during foreign language speech production. The article has been divided into two complementary parts. The first one introduces theoretical background to the issue of speaking, pronunciation and elicitation of oral language with the help of visuals and storytelling. The second one, on the other hand, describes the procedure as well as the results of the experimental study and a questionnaire survey that were conducted with a group of 15 secondary school students. The data point to the advantage of presentations over other types of oral performance both with respect to speaking and pronunciation practice as well as the students’ mental state. However, further research is necessary to prove the correctness of the above-mentioned statement.